Answer:
A
Step-by-step explanation:
is in the fourth quadrant where tan < 0
The related acute angle = 2π -
= ![\frac{\pi }{6}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cpi%20%7D%7B6%7D)
Hence
tan(
)
= - tan(
)
= - ![\frac{1}{\sqrt{3} }](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%5Csqrt%7B3%7D%20%7D)
= -
× ![\frac{\sqrt{3} }{\sqrt{3} }](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B3%7D%20%7D%7B%5Csqrt%7B3%7D%20%7D)
= -
→ A
Hello,
y=2^(-x)
y=2^(2x)+3
==>2^(2x)+3=1/2^x
==>2^(3x)+3*2^x-1=0 (1)
Let's assume u=2^x
(1)==>u^3+3*u-1=0
which as 3 roots
u=0.322185354626 or
u = -0.161092677313 + i1.754380959784 or
u = -0.161092677313 - i1.754380959784.
Let's take the real solution
0.322185354626=2^x
==>x=ln(0.322185354626) / ln(2)
x=-1,6340371790199...
an other way is
f(x)=2^(3x)+3*2^x-1
f(-2)=1/64+3/4-1=-15/64 <0
f(-1)=1/8+1-1=1/8>0
==> there is a solution betheen -2<x<-1
Answer:the third option is correct
Step-by-step explanation:
The system of equations are
y = 2x^2 - 5x - 7 - - - - - - - - - - -1
y = 2x + 2 - - - - - - - - - - - - - 2
We would equate equation 1 and equation 2. It becomes
2x^2 - 5x - 7 = 2x + 2
2x^2 - 5x - 2x - 7 - 2 = 0
2x^2 - 7x - 9 = 0
We would find two numbers such that their sum or difference is -7x and their product is - 18x^2. The two numbers are 2x and - 9x. Therefore
2x^2 + 2x - 9x - 9 = 0
2x(x + 1) - 9(x + 1) = 0
2x - 9 = 0 or x + 1 = 0
2x = 9 or x = - 1
x = 9/2 = 4.5
Substituting x = 4.5 or x = -1 into equation 2, it becomes
y = 2 × 4.5 + 2 or y = 2 × - 1 + 2
y = 11 or y = 0
Therefore, the solutions are
(4.5, 11) (- 1, 0)
Type one is genetic and you are born with it. type two is acquired through an unhealthy lifestyle such as eating junk food and not exercising regularly
Answer: 0
Step-by-step explanation:
![-\frac{2}{3}(x+5)+4(x+5)-\frac{10}{3}(x+5) = ?](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B3%7D%28x%2B5%29%2B4%28x%2B5%29-%5Cfrac%7B10%7D%7B3%7D%28x%2B5%29%20%3D%20%3F)
![-\frac{2}{3}x-\frac{10}{3}x+4x+20-\frac{10}{3}x-\frac{50}{3} = ?](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7B3%7Dx-%5Cfrac%7B10%7D%7B3%7Dx%2B4x%2B20-%5Cfrac%7B10%7D%7B3%7Dx-%5Cfrac%7B50%7D%7B3%7D%20%3D%20%3F)
![(-\frac{2}{3}x+4x -\frac{10}{3}x) +(-\frac{10}{3}+20-\frac{50}{3})=?](https://tex.z-dn.net/?f=%28-%5Cfrac%7B2%7D%7B3%7Dx%2B4x%20-%5Cfrac%7B10%7D%7B3%7Dx%29%20%2B%28-%5Cfrac%7B10%7D%7B3%7D%2B20-%5Cfrac%7B50%7D%7B3%7D%29%3D%3F)
![(-\frac{12}{3}x+4x)+(-\frac{60}{3}+20)=?\\ (-4x+4x)+(-20+20)=?\\0+0=0](https://tex.z-dn.net/?f=%28-%5Cfrac%7B12%7D%7B3%7Dx%2B4x%29%2B%28-%5Cfrac%7B60%7D%7B3%7D%2B20%29%3D%3F%5C%5C%20%20%28-4x%2B4x%29%2B%28-20%2B20%29%3D%3F%5C%5C0%2B0%3D0)